Regulation of cadherin expression in nervous system development - Paulson, Alicia F (Landes Bioscience, 2014)
This review addresses our current understanding of the regulatory mechanisms for classical cadherin expression during development of the vertebrate nervous system. The complexity of the spatial and temporal expression patterns is linked to morphogenic and functional roles in the developing nervous system. While the regulatory networks controlling cadherin expression are not well understood, it is likely that the multiple signaling pathways active in the development of particular domains also regulate the specific cadherins expressed at that time and location. With the growing understanding of the broader roles of cadherins in cell–cell adhesion and non-adhesion processes, it is important to understand both the upstream regulation of cadherin expression and the downstream effects of specific cadherins within their cellular context.